2009
DOI: 10.1007/s11665-009-9458-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiN Reinforced Aluminium Metal Matrix Composites Through Microwave Sintering

Abstract: Al-TiN (10, 20, 30 wt.%) composites were fabricated by using microwave radiation. Al and TiN powders were selected as starting materials, mixed in a ball mill for $10 min and sintered for various times. Results indicate that an optimum microwave sintering time of 2 min was essential and responsible for the improved densification and mechanical properties. The presence of TiN particles at grain boundaries plays a significant role in improving the densification and hardness values. Dry sliding wear results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…17 TiN was preferred as the reinforcement material in the aluminium alloy matrix and to avoid cluster behaviour in the melt, an optimum concentration of 10 wt% was selected. 18 Figure 1 displays the scanning electron microscope (SEM) image of as-received TiN reinforcement particles having an average particle size of 20 ± 10 µm. The matrix and reinforcing materials were supplied by M/s Coimbatore Metal Mart, India.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…17 TiN was preferred as the reinforcement material in the aluminium alloy matrix and to avoid cluster behaviour in the melt, an optimum concentration of 10 wt% was selected. 18 Figure 1 displays the scanning electron microscope (SEM) image of as-received TiN reinforcement particles having an average particle size of 20 ± 10 µm. The matrix and reinforcing materials were supplied by M/s Coimbatore Metal Mart, India.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…Results indicate that an optimum microwave sintering time of 2 min was essential and responsible for the improved densification and mechanical properties. The presence of TiN particles at grain boundaries plays a significant role in improving the densification and hardness values [18]. In the same year, Mondal et al investigated the feasibility of consolidating tungsten powders through microwave sintering.…”
Section: Microwave Sintering Of Al-mmcs -Historical Backgroundmentioning
confidence: 99%
“…Hence the PM products normally have superior properties over that of their cast counterparts. It was also reported that aluminum matrix composites processed via powder metallurgy technique exhibit good isotropic properties and green density greater than 90 % of theoretical density by using low compacting pressures between 200 to 250 MPa [14].…”
Section: Introductionmentioning
confidence: 99%